Strategi Pemanfaatan Curug Kali Mremang sebagai Destinasi Ekowisata di Desa Krajan, Kecamatan Pekuncen, Kabupaten Banyumas, Jawa Tengah - Zhafarini, Ghaziana; Dienaputra, Reiza D.; Rakhman, Cecep Ucu (Sekolah Vokasi, Universitas Gadjah Mada, 2024)
Krajan Village, located in Pekuncen District, Banyumas Regency, is rich in natural tourism potential. Situated at the foot of Mount Slamet, the village features Curug Kali Mremang, visible from the Central Java national pantura road, and other small waterfalls, sunrise viewpoints, and abundant spice crops thriving in the cool climate. Developing these attractions into ecotourism destinations can yield economic, social, and environmental conservation benefits. This study aims to identify the tourism potential in Krajan Village and strategies for developing Curug Kali Mremang in line with sustainable tourism principles. Using qualitative research methods, data were collected through tourist interviews and literature studies. Findings indicate that Krajan Village has significant natural and cultural tourism potential.The SWOT analysis suggests that Curug Kali Mremang's ecotourism development can be achieved through active village government collaboration to improve access, road infrastructure, signage, and develop amenities like parking and stalls. The site can offer educational tourism and unique attractions such as nature exploration, sunrise watching, and forest healing activities. Conservation efforts should include regulations to maintain ecological balance and prevent landslides. The traditional sedekah bumi (earth alms) festival can attract tourists and promote cultural participation. Leveraging the village's spice crops can create new income sources, boosting local businesses. Additionally, effective promotion and collaboration with conservationists and tourism operators can help Krajan Village reach a broader and more diverse audience, ensuring sustainable ecotourism development.